Wastewater Treatment on Shrimp Processing Industry - Alvin Rahardian Alviano; Sapto Andriyono (Journal of Marine and Coastal Science, 2020)
Increasingly rapid industrial development poses serious environmental problems such as wastewater.The higher the number of production, the more waste that wasted and can decrease the environment quality. Fieldwork practice activity is carried out starting from the date of January 20, 2014, until February 15, 2014. The purpose of this fieldwork practice is to acquire knowledge and skills on the field of wastewater treatment technique and to know the parameters of the wastewater inlet and outlet channels in comparison with wastewater quality standards. The method that used in Field Work Practice This is descriptive, the method to describe the circumstances or events in a particular region. The result obtained from fieldwork practice known that wastewater treatment techniques consist of preliminary treatment activities, primary treatment, secondary treatment, sedimentation, and disinfection. Preliminary treatment activities is a filtering process substantial in the wastewater that comes out of the inlet channel using four mesh size of the net. The primary treatment for separating solids that escaped from the screening process and disposed to wastewater reservoirs. Secondary treatment activity including Aerobacter sp., Nitrosomonas sp., Nitrobacter sp., Bacillus sp. of bacteria and oxygen addition inside of wastewater. Sedimentation phase separation process is carried out suspended solids in wastewater using clarifier pond. Disinfection stage which activities the addition of chlorine with 222 ppm of doses to kill harmful pathogens. The final stage test to determine the parameters of wastewater effluent quality by using living fishes and taking the sample from another institution.